Core-shell-shell three-stage structure composite material as well as preparation method and application thereof
By preparing a core-shell-shell three-level structure composite material, and combining upconversion micron particles, graphitic carbon nitride, and magnetic sepiolite, the problem of low photocatalytic efficiency of existing nanomaterials was solved, achieving efficient degradation of organic pollutants and improving the material's cycle stability and recycling efficiency.
Patent Information
- Application Number
- CN202511416869.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2045-09-30
AI Technical Summary
Existing single nanomaterials have low photocatalytic efficiency and narrow spectral response range, making it difficult to effectively degrade pollutants.
A core-shell-shell three-level composite material is adopted, which includes the ternary synergy of upconversion micron particles, graphitic carbon nitride and magnetic sepiolite. The core-shell-shell structure is formed by a one-step calcination method combined with a co-precipitation method, and the electron-hole separation efficiency is improved by the interface self-assembly.
Significantly improving photocatalytic efficiency and cycle stability, the material increases the degradation efficiency of organic pollutants by more than 257% under simulated sunlight, and can be quickly recycled and reused through an external magnetic field.
Smart Images

Figure CN120885258A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of photocatalytic functional materials, and particularly relates to a core-shell-shell three-level structure composite material and a preparation method and application thereof. BACKGROUND
[0002] Photocatalytic technology uses solar energy as driving force, realizes pollutant degradation and CO2 resource conversion through nanomaterial-mediated redox reaction, and provides a sustainable path for the conversion of ecological value to economic value. Compared with the high-temperature energy consumption of incineration treatment and the saturation failure defect of adsorption technology, photocatalytic nanoparticles can realize the targeted activation of pollutant molecules at room temperature and normal pressure, avoid the generation of by-products and additional energy input, due to their high specific surface area, adjustable electronic structure and multi-phase interface activity. The existing single nanomaterial has problems of narrow spectral response range and low photocatalytic efficiency. SUMMARY
[0003] In order to solve the above technical problems, the application provides a core-shell-shell three-level structure composite material and a preparation method and application thereof. The core-shell-shell three-level structure composite material has ternary synergy of upconversion microparticles, graphite phase carbon nitride and magnetic sepiolite, which significantly improves the photocatalytic efficiency and cycle stability.
[0004] To achieve the above purpose, the application first provides a core-shell-shell three-level structure composite material, which comprises upconversion microparticles, graphite phase carbon nitride and magnetic sepiolite; the upconversion microparticles are the core, the graphite phase carbon nitride is the intermediate shell layer, and the magnetic sepiolite is the outer shell layer; the upconversion microparticles comprise Yb and Tm doped β-NaYF4.
[0005] In some embodiments, the molar ratio of β-NaYF4, Yb and Tm in the upconversion microparticles is (0.79-0.8):(0.2-0.21):(0.01-0.02); further, the molar ratio of β-NaYF4, Yb and Tm is 0.79:0.2:0.01.
[0006] In some embodiments, the upconversion microparticles are β-NaYF4, 20% Yb and 1% Tm. Among them, β-NaYF4, 20% Yb and 1% Tm mean that in β-NaYF4, 20% Yb and 1% Tm, the molar ratio of β-NaYF4 is 79%, the molar ratio of Yb is 20%, and the molar ratio of Tm is 1%.
[0007] In some embodiments, the particle size of the composite material is 3-5 μm.
[0008] In some embodiments, the mass ratio of the upconversion microparticles, graphite phase carbon nitride and magnetic sepiolite of the composite material is 1:1:0.5.
[0009] Based on a total inventive concept, the application also provides a preparation method of a core-shell-shell three-level structure composite material, comprising the following steps: Step 1, mix sodium citrate solution, yttrium nitrate solution, ytterbium nitrate solution and thulium nitrate solution, stir at 500 rpm~600 rpm for 20 min~25 min, drop sodium fluoride solution, then stir for 30 min~35 min, then transfer the mixed solution to a polytetrafluoroethylene lined autoclave, and perform hydrothermal reaction at 200℃~205℃ for 24 h~25 h; the obtained precipitate is washed, dried, and annealed at 500℃~510℃ for 2 h~2.5 h in a nitrogen atmosphere to obtain upconversion microparticles; Step 2, mix and grind the upconversion microparticles with urea, then calcine to obtain an upconversion microparticle@g-C3N4 core-shell structure material.
[0010] Step 3: prepare a mixed solution by adding FeCl3·6H2O and FeSO4·7H2O in deionized water, stir to dissolve, then add sepiolite, heat to 60℃~65℃ at a rate of 5℃ / min~6℃ / min under argon protection, add concentrated ammonia water dropwise to adjust the pH to 9.5~10.5 after magnetic stirring for 10 min~20 min, continue to react for 1 h~1.5 h; then age in a vacuum environment at 35℃~40℃ for 1.5 h~2.5 h; after aging, wash with deionized water and ethanol alternately for 3~4 times, and vacuum dry to obtain magnetic sepiolite; Step 4: disperse the magnetic sepiolite and the upconversion microparticle@g-C3N4 core-shell structure material obtained in step 2 in deionized water respectively, heat the dispersion of the magnetic sepiolite to 55℃~65℃, and add the dispersion of the upconversion microparticle@g-C3N4 core-shell structure material dropwise under stirring, continue to stir for 2 h~3 h after the addition is completed, and dry the precipitate obtained by centrifugation to obtain a core-shell-shell three-level structure composite material.
[0011] In some embodiments, in step 1, the molar ratio of sodium citrate, yttrium nitrate, ytterbium nitrate, thulium nitrate and sodium fluoride is 1:(0.79~0.8):(0.2~0.21):(0.01~0.02):(12~12.1).
[0012] In some embodiments, in step 1, the dropwise addition rate of the sodium fluoride solution is 0.03 ml / s~0.05 ml / s. By controlling the dropwise addition rate of the sodium fluoride solution, the morphology of the upconversion microparticles can be controlled to be more uniform.
[0013] In some embodiments, in step 1, the concentration of the sodium citrate solution is 0.3 mol / L, the concentration of the Y(NO3)3 solution is 0.208 mol / L, the concentration of the Yb(NO3)3 solution is 0.24 mol / L, the concentration of the Tm(NO3)3 solution is 0.048 mol / L, and the concentration of the NaF solution is 0.5 mol / L.
[0014] In some embodiments, in step 2, the mass ratio of the upconversion microparticles to urea is 1:(1-10); preferably, the mass ratio of the upconversion microparticles to urea is 1:(5-7); further preferably, the mass ratio of the upconversion microparticles to urea is 1:(6.6-6.62).
[0015] In some embodiments, in step 2, the calcination step includes heating to 500-600°C at a rate of 4-6°C / min and calcining for 4-5h. Preferably, heating to 550°C at a rate of 5°C / min and calcining for 4h.
[0016] In some embodiments, in step 3, the total molar concentration of FeCl3·6H2O and FeSO4·7H2O in the mixed solution prepared from FeCl3·6H2O and FeSO4·7H2O is 0.3 mol / L.
[0017] In some embodiments, the molar ratio of FeCl3·6H2O to FeSO4·7H2O is (1-3):1; preferably, the molar ratio of FeCl3·6H2O to FeSO4·7H2O is (1.74-1.76):1. By controlling the ratio of Fe 3+ to Fe 2+ , the magnetic properties and stability of the product are improved.
[0018] In some embodiments, the ratio of the total mass of FeCl3·6H2O and FeSO4·7H2O to the mass of sepiolite is (0.8-0.9):1. Preferably, the ratio of the total mass of FeCl3·6H2O and FeSO4·7H2O to the mass of sepiolite is (0.81-0.82):1.
[0019] In some embodiments, in step 4, the mass ratio of the magnetic sepiolite to the upconversion microparticle@g-C3N4 core-shell structure material is 1:(1-10). Preferably, the mass ratio of the magnetic sepiolite to the upconversion microparticle@g-C3N4 core-shell structure material is 1:(1-5); further preferably, the mass ratio of the magnetic sepiolite to the upconversion microparticle@g-C3N4 core-shell structure material is 1:4.
[0020] In some embodiments, in step 4, the dropwise adding speed of the dispersion liquid of the upconversion microparticle @ g-C3N4 core-shell structure material is 0.03 ml / s to 0.05 ml / s.
[0021] Based on the overall inventive concept, the application further provides an application of the core-shell-shell three-level structure composite material in photocatalytic degradation and removal of organic pollutants in water.
[0022] In some embodiments, the application of the core-shell-shell three-level structure composite material in photocatalytic degradation and removal of organic pollutants in water comprises the following steps: The core-shell-shell three-level structure composite material is mixed with a solution to be degraded, and placed in dark conditions for 30 min to 40 min; then degradation is carried out under light irradiation.
[0023] In some embodiments, the light irradiation condition is irradiation under 980 nm near-infrared light or irradiation under simulated sunlight.
[0024] In some embodiments, the organic pollutant is ofloxacin.
[0025] In some embodiments, the concentration of the organic pollutant in the solution to be degraded is ≤500 μmol / L.
[0026] In some embodiments, the pH value of the solution to be degraded is 6.5 to 10.
[0027] The photocatalytic degradation mechanism of the core-shell-shell three-level structure nanocomposite material prepared by the application is as follows: The above upconversion microparticles (UCMPs) are used as the core, graphite phase carbon nitride g-C3N4 is used as the intermediate shell layer, and magnetic sepiolite (MSEP) is used as the outer shell layer. The UCMPs and g-C3N4 core-shell combination is realized by a one-step calcination method, the sepiolite is magnetically modified by a coprecipitation method, and finally the core-shell-shell three-level structure is formed by interface self-assembly. The heterojunction structure is formed by the core and the intermediate shell layer, the driving force brought by the built-in electric field is used to realize the electronic-hole separation in space scale, the lifetime of the photo-generated carriers is effectively prolonged, more effective charges are provided for the photocatalytic reaction, and the photocatalytic performance is improved. Further, in the UCMPs@g-C3N4@MSEP material, the UCMPs can absorb near-infrared light to convert into visible light which is then absorbed by the g-C3N4, the g-C3N4 can absorb light less than 500 nm in simulated sunlight to generate reactive oxygen species for degradation of antibiotics. The MSEP is the outermost layer, on the one hand, the sepiolite can improve the hydrophilicity of the material and actively adsorb pollutants in wastewater, so that the pollutants can be effectively degraded; on the other hand, the magnetism can improve the recycling efficiency. Finally, the core-shell-shell structure design can inhibit the exciton recombination of the material and improve the photocatalytic efficiency.
[0028] Compared with the prior art, the application has the following beneficial effects: (1) The application realizes the core-shell combination of UCMPs and g-C3N4 by one-step calcination method, and the magnetic modification of sepiolite is realized by co-precipitation method, and finally the core-shell-shell structure is formed by interface self-assembly, the UCMPs are the core, the graphite phase carbon nitride g-C3N4 is the intermediate shell layer, and the magnetic sepiolite (MSEP) is the outer shell layer, the process is simple, the cost is low, and it is suitable for large-scale production.
[0029] (2) The material prepared by the application has photocatalytic activity and magnetic separation performance, the degradation efficiency of organic pollutants under simulated sunlight is improved by more than 257% compared with single component, and the material can be quickly recycled and reused through an external magnetic field. BRIEF DESCRIPTION OF DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the application or the prior art, the drawings needed to be used in the embodiments or the prior art description will be briefly introduced below. Obviously, the drawings in the following description are some embodiments of the application, and other drawings can also be obtained by those skilled in the art without creative labor.
[0031] Figure 1 X-ray powder diffraction (XRD) test results of UCMPs@g-C3N4@MSEP prepared in Example 1, UCMPs, MSEP, and g-C3N4 prepared in Comparative Example 1.
[0032] Figure 2 SEM and mapping energy spectrum diagrams of UCMPs, UCMPs@g-C3N4 and UCMPs@g-C3N4@MSEP prepared in Example 1; wherein (a) is the SEM diagram of UCMPs, (b) is the SEM diagram of UCMPs@g-C3N4, (c) is the SEM diagram of UCMPs@g-C3N4@MSEP, (d) is the mapping diagram of Y element in UCMPs, (e) is the mapping diagram of N element in UCMPs@g-C3N4, and (f) is the mapping diagram of Si element in UCMPs@g-C3N4@MSEP.
[0033] Figure 3 Water contact angle test results of UCMPs, UCMPs@g-C3N4 and UCMPs@g-C3N4@MSEP prepared in Example 1; wherein (a) is the water contact angle test diagram of UCMPs, (b) is the water contact angle test diagram of UCMPs@g-C3N4, and (c) is the contact angle test diagram of UCMPs@g-C3N4@MSEP.
[0034] Figure 4 The magnetic performance of UCMPs@g-C3N4 and UCMPs@g-C3N4@MSEP prepared in Example 1 was tested, and the results are shown in the following figures.
[0035] Figure 5 UCMPs@g-C3N4@MSEP, UCMPs@g-C3N4 prepared in Example 1 and g-C3N4 prepared in Comparative Example 1 were subjected to scanning Kelvin probe force microscopy (KPFM) test, and the results are shown in the following figures, wherein Figure 5 (a) is a surface potential two-dimensional mapping of g-C3N4 under dark conditions, (b) is a surface potential two-dimensional mapping of g-C3N4 under light conditions, (c) is a local area potential line distribution curve of g-C3N4, (d) is a surface potential two-dimensional mapping of UCMPs@g-C3N4 under dark conditions, (e) is a surface potential two-dimensional mapping of UCMPs@g-C3N4 under light conditions, (f) is a local area potential line distribution curve of UCMPs@g-C3N4, (g) is a surface potential two-dimensional mapping of UCMPs@g-C3N4 under dark conditions, (h) is a surface potential two-dimensional mapping of UCMPs@g-C3N4 under light conditions, and (i) is a local area potential line distribution curve of UCMPs@g-C3N4.
[0036] Figure 6 UCMPs@g-C3N4@MSEP and UCMPs@g-C3N4 prepared in Example 1 were subjected to photocurrent response test, and the results are shown in the following figures.
[0037] Figure 7 The photocatalytic degradation effect of g-C3N4 and UCMPs@g-C3N4 on 400 μmol / L ofloxacin under near-infrared light is shown in the following figures.
[0038] Figure 8 The photocatalytic degradation effect of each component material on 400 μmol / L ofloxacin under simulated sunlight and the fitting kinetic curve are shown in the following figures, wherein (a) is the photocatalytic degradation effect of each component material on 400 μmol / L ofloxacin under simulated sunlight; and (b) is the fitting kinetic curve.
[0039] Figure 9 The degradation effect of UCMPs@g-C3N4@MSEP on different concentrations of ofloxacin is shown in the following figures.
[0040] Figure 10Figure for degradation effect of ofloxacin by UCMPs@g-C3N4@MSEP under different pH conditions.
[0041] Figure 11 Figure for results of cycle stability test of UCMPs@g-C3N4@MSEP. DETAILED DESCRIPTION
[0042] In order to make the technical problems, technical solutions and advantages of the present application clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments.
[0043] The following examples are intended to illustrate the present application but not to limit the scope of the present application. Modifications or replacements of the methods, steps or conditions of the present application, without departing from the spirit and essence of the present application, all belong to the scope of the present application.
[0044] If not specifically indicated, the technical means used in the examples are conventional means known to those skilled in the art; if not specifically indicated, the reagents used in the examples are commercially available.
[0045] Example 1 Preparation of nanocomposite UCMPs@g-C3N4@MSEP with core-shell-shell tertiary structure.
[0046] Step 1, synthesis of β-NaYF4:20%Yb, 1%Tm upconversion microparticles (UCMPs) by hydrothermal method: in a 50 mL beaker, 4 mL of sodium citrate solution with a concentration of 0.3 mol / L was mixed with 4.6 mL of Y(NO3)3 solution with a concentration of 0.208 mol / L, 1.0 mL of Yb(NO3)3 solution with a concentration of 0.24 mol / L and 0.25 mL of Tm(NO3)3 solution with a concentration of 0.048 mol / L, and the stirring was continued for 20 minutes at a stirring rate of 500 rpm. Then, 29 mL of NaF solution with a concentration of 0.5 mol / L was added dropwise, and the stirring was continued for 30 minutes after 10 minutes of dropwise addition. Then, the mixture was transferred to a polytetrafluoroethylene-lined reaction kettle, and hydrothermal reaction was carried out at 200 ℃ for 24 hours. The obtained precipitate was washed and dried, and then annealed at 500 ℃ for 2 hours under a nitrogen atmosphere to obtain UCMPs.
[0047] Step 2, preparation of UCMPs@g-C3N4 core-shell structure composite: 300 mg of UCMPs was mixed with 1.985 g of urea in a agate mortar and ground for 5 minutes, and then transferred to a ceramic crucible and covered with a lid. Then, the mixture was placed in a muffle furnace and heated to 550 ℃ at a rate of 5 ℃ / min, and calcined for 4 hours. After natural cooling, UCMPs@g-C3N4 particles were obtained; in the UCMPs@g-C3N4 particles, the mass ratio of UCMPs to g-C3N4 was 1:1.
[0048] Step 3, preparation of magnetic sepiolite MSEP: 1.0328 g of FeCl3·6H2O and 0.6066 g of FeSO4·7H2O were added to 25 ml of deionized water, and after stirring and dissolving, the solution was transferred to a 250 ml three-necked round-bottom flask and 2 g of sepiolite was added. After rapid heating to 60°C under argon protection and magnetic stirring for 15 minutes, concentrated ammonia was added dropwise to adjust the pH to 10, and the reaction was continued for 1 hour. After the reaction was completed, the product was placed in a vacuum drying oven and heated to 35°C under vacuum for 2 hours. After aging, the product was washed with deionized water and ethanol alternately for 3 times, and then placed in a vacuum drying oven and heated to 60°C under vacuum for drying. After the product was completely dried, it was ground into powder for use, and MSEP was obtained.
[0049] Step 4, preparation of UCMPs@g-C3N4@MSEP composite photocatalyst: 25 mg of MSEP was dispersed in deionized water and ultrasonicated for 30 minutes, and 100 mg of UCMPs@g-C3N4 was dispersed in deionized water and ultrasonicated for 30 minutes. After the dispersion was completed, the MSEP dispersion was heated to 60°C and stirred using a mechanical stirring device. After the stirring started, the UCMPs@g-C3N4 dispersion was added dropwise to the MSEP dispersion, and stirred for 2 hours. The precipitate was collected by centrifugation and dried at 60°C to obtain the UCMPs@g-C3N4@MSEP composite material.
[0050] Comparative Example 1 Preparation of g-C3N4 particles: 1.985 g of urea was mixed and ground in a agate mortar for 5 minutes, then transferred to a ceramic crucible and covered with a lid, and then placed in a muffle furnace and heated to 550°C at a rate of 5°C / min for 4 hours. After natural cooling, g-C3N4 particles were obtained.
[0051] Performance test and analysis: XRD test: UCMPs@g-C3N4@MSEP, UCMPs, g-C3N4 and MSEP were subjected to XRD test analysis, and the results are shown in Figure 1 From Figure 1 it can be seen that the characteristic absorption peaks of UCMPs, g-C3N4 and MSEP correspond to the characteristic absorption peaks of UCMPs@g-C3N4@MSEP.
[0052] SEM and mapping energy spectrum test: UCMPs, UCMPs@g-C3N4 and UCMPs@g-C3N4@MSEP prepared in Example 1 were subjected to SEM test and mapping energy spectrum analysis, respectively. The specific results are shown in Figure 2 Figure 2 (a) is the SEM image of UCMPs, (b) is the SEM image of UCMPs@g-C3N4, (c) is the SEM image of UCMPs@g-C3N4@MSEP, (d) is the mapping image of Y element in UCMPs, (e) is the mapping image of N element in UCMPs@g-C3N4, and (f) is the mapping image of Si element in UCMPs@g-C3N4@MSEP. It can be seen from the figures that Y, N and Si elements are uniformly distributed, Y is the main component element of UCMPs, N is the main element of g-C3N4, and Si is the main element of MSEP, so the uniform and same area distribution of the three elements also indicates the construction of the core-shell-shell structure.
[0053] Water contact angle test: the water contact angle test was performed on the UCMPs, UCMPs@g-C3N4 and UCMPs@g-C3N4@MSEP prepared in Example 1, respectively, and the results are shown in Figure 3 , wherein (a) is the water contact angle test image of UCMPs, (b) is the water contact angle test image of UCMPs@g-C3N4, and (c) is the contact angle test image of UCMPs@g-C3N4@MSEP. It can be seen from the figures that the water contact angle of UCMPs is 134.5°, the water contact angle of UCMPs@g-C3N4 is 43.5°, and the contact angle of UCMPs@g-C3N4@MSEP is 18.1°. It can be seen that UCMPs@g-C3N4@MSEP has good hydrophilicity.
[0054] Magnetic property test: the magnetic properties of UCMPs@g-C3N4 and UCMPs@g-C3N4@MSEP prepared in Example 1 were tested, the relationship between the magnetization intensity of the material and the magnetic field intensity in the periodically changing external magnetic field was observed, and the hysteresis loop curve was drawn, and the results are shown in Figure 4 . In the test results of the hysteresis loop, the ordinate of the hysteresis loop curve of UCMPs@g-C3N4@MSEP is higher than that of UCMPs@g-C3N4, which indicates that after the surface of UCMPs@g-C3N4 is wrapped with MSEP shell, the magnetic property of the composite material is improved. The improvement of the magnetic property can enhance the recovery efficiency of the composite material during photocatalytic degradation.
[0055] Kelvin voltage test: the scanning Kelvin probe microscope (KPFM) test was performed on UCMPs@g-C3N4@MSEP prepared in Example 1, UCMPs@g-C3N4 and g-C3N4 prepared in Comparative Example 1, respectively, the surface potential distribution and the light-induced charge separation related performance of the material were observed under dark (Dark) and light (Light) conditions, and the two-dimensional mapping image of the surface potential and the local area potential line distribution curve were collected. The results are shown inFigure 5 As shown, where Figure 5 (a) is a two-dimensional mapping of the surface potential of g-C3N4 under dark conditions; (b) is a two-dimensional mapping of the surface potential of g-C3N4 under light conditions; (c) is a local potential line distribution curve of g-C3N4; (d) is a two-dimensional mapping of the surface potential of UCMPs@g-C3N4 under dark conditions; (e) is a two-dimensional mapping of the surface potential of UCMPs@g-C3N4 under light conditions; (f) is a local potential line distribution curve of UCMPs@g-C3N4; (g) is a two-dimensional mapping of the surface potential of UCMPs@g-C3N4@MSEP under dark conditions; (h) is a two-dimensional mapping of the surface potential of UCMPs@g-C3N4@MSEP under light conditions; and (i) is a local potential line distribution curve of UCMPs@g-C3N4@MSEP. Figure 5 As can be seen, the g-C3N4 sample exhibits a negative surface photovoltage (SPV = -25.35 mV), confirming its typical n-type semiconductor characteristics, where photoexcited electrons migrate to the bulk phase while holes accumulate on the surface. Although this charge separation mode is beneficial for surface oxidation reactions, the relatively low absolute SPV value indicates a considerable degree of charge recombination, thus limiting the photocatalytic efficiency. In contrast, the UCMPs@g-C3N4 composite material exhibits a positive SPV response (+40.84 mV) under illumination, indicating a reversal of the electron transfer direction. This is likely due to the built-in electric field at the interface formed by the UCMP incorporation, which promotes electron migration to the surface while suppressing charge recombination. Further modification with MSEP (i.e., UCMPs@g-C3N4@MSEP) increases the SPV to +42.36 mV, indicating a further reduction in charge recombination. The above KPFM analysis shows that the core-shell-shell structure design significantly improves the exciton separation efficiency.
[0056] Photocurrent response testing: Photocurrent response tests were performed on the UCMPs@g-C3N4@MSEP and UCMPs@g-C3N4 prepared in Example 1. Periodic "illuminated-dark" cycling conditions were set up to observe the photoelectric conversion and photogenerated carrier separation / recombination kinetics under alternating illumination and darkness conditions. The photocurrent intensity, response speed, and cycling stability were analyzed by the periodic change of current density over time. The results are as follows: Figure 6 As shown. From Figure 6It can be seen that although both UCMPs@g-C3N4 and UCMPs@g-C3N4@MSEP exhibit fast photocurrent switching response, the photocurrent density of UCMPs@g-C3N4@MSEP composite is increased by 43%, which directly proves the improvement of charge separation efficiency, because the size of photocurrent is directly related to the number of photo-generated carriers successfully migrated to the electrode surface without recombination. This improvement is due to the hierarchical interface effect in the core-shell-shell structure, which helps to separate electrons and holes. The test results of photocurrent response test are consistent with the conclusion that the core-shell-shell structure design significantly improves the efficiency of exciton separation in KPFM analysis.
[0057] Application Example 1 30 mg of UCMPs@g-C3N4 prepared in Example 1 and 30 mg of g-C3N4 prepared in Comparative Example 1 were respectively mixed with 40 mL of an ofloxacin aqueous solution with a concentration of 400 μmol / L (pH = 7) uniformly, and were placed in the dark for 30 min. Then, under the irradiation of 980 nm 1.5 W / cm 2 Under the irradiation of near-infrared laser, the photodegradation experiment was carried out, and the concentration of ofloxacin in the two groups of mixed solutions was recorded every 10 min, and the results are shown in Figure 7 .
[0058] Application Example 2 30 mg of UCMPs@g-C3N4@MSEP, UCMPs, MSEP, UCMPs@g-C3N4 prepared in Example 1 and g-C3N4 prepared in Comparative Example 1 were respectively mixed with 40 mL of an ofloxacin aqueous solution with a concentration of 400 μmol / L (pH = 7) uniformly, and were placed in the dark for 30 min. Then, under the irradiation of simulated sunlight (100 mW / cm 2 ), the photodegradation experiment was carried out, and the concentration of ofloxacin in each group of mixed solutions was recorded every 10 min, and the results are shown in Figure 8 (a).
[0059] Then the degradation kinetics of each component was calculated according to Figure 8 (a), and the results are shown in Figure 8 (b).
[0060] Application Example 3 30 mg of UCMPs@g-C3N4@MSEP prepared in Example 1 were respectively mixed with 40 mL of an ofloxacin aqueous solution with a concentration of 200 μmol / L, 300 μmol / L, 400 μmol / L and 500 μmol / L (pH = 7), and after being placed in the dark for 30 min, the photodegradation experiment was carried out under the irradiation of simulated sunlight, and the concentration of ofloxacin in each group of mixed solutions was recorded every 10 min, and the results are shown in Figure 9 .
[0061] Application Example 4 30 mg of UCMPs@g-C3N4@MSEP prepared in Example 1 was mixed with 40 mL of ofloxacin aqueous solutions with pH values of 3, 5, 7, and 9 and a concentration of 400 μmol / L, respectively. After standing in the dark for 30 min, photodegradation experiments were conducted under simulated sunlight. The concentration of ofloxacin in each mixed solution was recorded every 10 min. The results are as follows: Figure 10 As shown.
[0062] Application Example 5 30 mg of UCMPs@g-C3N4@MSEP was mixed with 40 mL of ofloxacin solution at a concentration of 400 mol / L (pH=7). After standing in the dark for 30 min, a photodegradation experiment was conducted under simulated sunlight, and the concentration was recorded every 10 min. This cyclic experiment was repeated 5 times. After each reaction, the catalyst was recovered, dried, and replenished to the initial mass to evaluate its degradation stability. The results are as follows: Figure 11 As shown.
[0063] Combination Figures 7-8 To conduct analysis, from Figure 7 As can be seen, when combined with UCMPs, the UCMPs in UCMPs@g-C3N4 can convert 980nm near-infrared light into visible light. The visible light is then absorbed by g-C3N4, generating reactive oxygen species, thus producing the ability to photocatalytically degrade ofloxacin. However, g-C3N4 alone cannot absorb 980nm light, so it has no degradation effect in this case. Figure 8 Figure (a) shows the degradation results of various materials for ofloxacin under simulated sunlight, with UCMPs@g-C3N4@MSEP showing the best degradation effect. Figure (b) is the first-order kinetic curve corresponding to Figure (a). As can be seen from Figure (b), UCMPs@g-C3N4@MSEP has the fastest degradation rate. Figure 9 The graph shows the degradation effect of UCMPs@g-C3N4@MSEP on different concentrations of ofloxacin. Figure 9 It can be seen that the lower the concentration, the better the degradation effect; when the concentration exceeds 500 μM, the degradation effect decreases. Figure 10 The graph shows the degradation effect of ofloxacin by UCMPs@g-C3N4@MSEP under different pH conditions. The degradation effect is very good under acidic and neutral conditions, while the degradation effect decreases under alkaline conditions. Figure 11 The figure shows the cyclic stability test results of UCMPs@g-C3N4@MSEP. UCMPs@g-C3N4@MSEP degraded ofloxacin in 5 cycles, maintaining a degradation efficiency of over 97%; it has good stability and high recovery rate.
[0064] Example 2
[0065] The preparation method of this example is basically the same as that of Example 1, the only difference is that the mass ratio of magnetic sepiolite and upconversion microparticle @ g-C3N4 core-shell structure material is different, and the use amount ratio of MSEP and UCMPs @ g-C3N4 in this example is 1:2.
[0066] Example 3
[0067] The preparation method of this example is basically the same as that of Example 1, the only difference is that the mass ratio of magnetic sepiolite and upconversion microparticle @ g-C3N4 core-shell structure material is different, and the use amount ratio of MSEP and UCMPs @ g-C3N4 in this example is 1:10.
[0068] Example 4
[0069] The preparation method of this example is basically the same as that of Example 1, the only difference is that the mass ratio of UCMPs and urea in step 2 is different, and the mass ratio of UCMPs and urea in step 2 of this example is 1:1.
[0070] Example 5
[0071] The preparation method of this example is basically the same as that of Example 1, the only difference is that the mass ratio of UCMPs and urea in step 2 is different, and the mass ratio of UCMPs and urea in step 2 of this example is 1:10.
[0072] UCMPs @ g-C3N4 @ MSEP 0.01 g prepared in Examples 1-4 were mixed with 20 mL of 200 μmoL / L concentration ofloxacin aqueous solution (pH = 7) respectively, placed in the dark for 30 min, and then photocatalytic degradation under simulated sunlight (100 mW / cm 2 ) for 40 min, and the degradation rate of UCMPs @ g-C3N4 @ MSEP prepared in each example on ofloxacin was recorded; wherein the degradation rate = (ofloxacin concentration initial concentration C0- ofloxacin concentration after degradation C) / ofloxacin initial concentration C0*100%. The results are shown in Table 1:
[0073] As can be seen from Table 1, the UCMPs@g-C3N4@MSEP prepared in Examples 1-5 all have a certain degradation effect on ofloxacin. Compared with Example 1, the proportion of UCMPs@g-C3N4 in Example 2 is reduced, and the degradation rate is reduced due to the significant reduction of g-C3N4 which produces active oxygen species. Compared with Example 1, the proportion of UCMPs@g-C3N4 in Example 3 is increased, and the degradation rate is reduced because the amount of MSEP is not enough to cover all UCMPs@g-C3N4, resulting in an increase in material charge recombination speed and a decrease in exciton separation efficiency; in addition, the decrease in the amount of MSEP reduces the hydrophilicity of the material, affecting the dispersion effect of the material in water. In Example 4, the mass ratio of UCMPs to urea is reduced, resulting in a decrease in the proportion of g-C3N4 in UCMPs@g-C3N4@MSEP, and the degradation rate is reduced because the decrease in the mass ratio of urea reduces the generation of g-C3N4. In Example 5, the UCMPs@g-C3N4@MSEP prepared has a higher content of g-C3N4, resulting in a decrease in the uniformity of the core-shell UCMPs@g-C3N4 structure, and thus when coated with MSEP, the core-shell-shell three-level structure is not as good as that of Example 1, and the inhibition effect of charge recombination is reduced, so the degradation rate is reduced compared with Example 1.
[0074] The preferred embodiments of the present application are described above, but the protection scope of the present application is not limited to the above examples. Improvements and changes made by those skilled in the art without departing from the technical concept of the present application should also be considered as within the protection scope of the present application.
Claims
1. A core-shell-shell tertiary structure composite material, characterized by, The core-shell-shell three-level structure composite material comprises up-conversion microparticles, graphite phase carbon nitride and magnetic sepiolite; the up-conversion microparticles are the core, the graphite phase carbon nitride is the intermediate shell layer, and the magnetic sepiolite is the outer shell layer; the up-conversion microparticles comprise Yb and Tm doped β-NaYF4.
2. The composite material of claim 1, wherein, In the up-conversion microparticles, the molar ratio of the β-NaYF4, Yb and Tm is (0.79-0.8):(0.2-0.21):(0.01-0.02).
3. The composite material of claim 1, wherein, The particle size of the composite material is 3-5 μm; and the mass ratio of the up-conversion microparticles to the graphite phase carbon nitride and the magnetic sepiolite is 1:1:0.
5.
4. A method of producing a composite material as claimed in any one of claims 1 to 3, characterised in that, The preparation method comprises the following steps: Step 1: a sodium citrate solution, a yttrium nitrate solution, a ytterbium nitrate solution, a thulium nitrate solution and a sodium fluoride solution are mixed, stirred at 500-600 rpm for 20-25 min, and then the sodium fluoride solution is added dropwise, followed by stirring for 30-35 min; then the mixed solution is transferred into a polytetrafluoroethylene lined autoclave, and subjected to hydrothermal reaction at 200-205 ℃ for 24-25 h; the obtained precipitate is washed, dried, and annealed at 500-510 ℃ for 2-2.5 h in a nitrogen atmosphere to obtain the up-conversion microparticles; Step 2: the up-conversion microparticles are mixed with urea, ground, calcined, and cooled to obtain the up-conversion microparticle@g-C3N4 core-shell structure material; Step 3: FeCl3·6H2O and FeSO4·7H2O are dissolved in deionized water to prepare a mixed solution, and then sepiolite is added; under argon protection, the temperature is raised to 60-65 ℃ at a rate of 5-6 ℃ / min, and then the mixed solution is stirred for 10-20 min; then concentrated ammonia water is added dropwise to adjust the pH to 9.5-10.5, and the reaction is continued for 1-1.5 h; then the mixture is aged in a vacuum environment at 35-40 ℃ for 1.5-2.5 h; after aging, the mixture is washed with deionized water and ethanol alternately for 3-4 times, and then vacuum dried to obtain the magnetic sepiolite; Step 4: the magnetic sepiolite and the up-conversion microparticle@g-C3N4 core-shell structure material obtained in step 2 are dispersed in deionized water respectively; the dispersion of the magnetic sepiolite is heated to 55-65 ℃, and the dispersion of the up-conversion microparticle@g-C3N4 core-shell structure material is added dropwise under stirring; after the dropwise addition is completed, the stirring is continued for 2-3 h; the precipitate is obtained by centrifugation and dried to obtain the core-shell-shell three-level structure composite material.
5. The preparation method according to claim 4, characterized in that, In step 1, the molar ratio of sodium citrate, yttrium nitrate, ytterbium nitrate, thulium nitrate and sodium fluoride is 1:(0.79-0.8):(0.2-0.21):(0.01-0.02):(12-12.1).
6. The preparation method according to claim 4, characterized in that, The mass ratio of the up-conversion microparticles to the urea is 1:(1-10).
7. The preparation method according to claim 4, characterized in that, The calcination step in step 2 comprises heating at a rate of 4-6 ℃ / min to 500-600 ℃ for 4-5 h.
8. The preparation method according to claim 4, characterized in that, The preparation method satisfies at least one of the following conditions: (1) the total molar concentration of the FeCl3·6H2O and the FeSO4·7H2O in the mixed solution prepared from the FeCl3·6H2O and the FeSO4·7H2O is 0.3 mol / L; (2) the molar ratio of the FeCl3·6H2O to the FeSO4·7H2O is (1-3):1; (3) the ratio of the total mass of the FeCl3·6H2O and the FeSO4·7H2O to the mass of the sepiolite is (0.8-0.9):
1.
9. The preparation method according to claim 4, characterized in that, In step 4, the mass ratio of the magnetic sepiolite to the upconversion microparticle @ g-C3N4 core-shell structure material is 1:(1-10).
10. Application of the core-shell-shell three-level structure composite material according to any one of claims 1-3 or prepared by the preparation method according to any one of claims 4-9 in photocatalytic degradation and removal of organic pollutants in water.
Citation Information
Patent Citations
Magnetic core-shell bismuth sub-carbonate / sepiolite composite photocatalyst and preparation method thereof
CN112808287A
Preparation method of sepiolite-carbon nitride composite photocatalyst as well as product and application of sepiolite-carbon nitride composite photocatalyst
CN115739159A